2012
DOI: 10.1039/c2dt30304c
|View full text |Cite
|
Sign up to set email alerts
|

Metal substitution in a Lindqvist polyoxometalate leads to improved photocatalytic performance

Abstract: The photochemical properties of homo- and heterometallic molybdate-based Lindqvist polyoxometalate clusters are investigated in a comparative study and it is shown that vanadium substitution can be used as a facile synthetic tool to optimize the visible light absorption and photocatalytic activity of the cluster. The mono-vanadium substituted unit, [VMo(5)O(19)](3-) shows light absorption up to 480 nm whereas the light absorption of the molybdate analogue [Mo(6)O(19)](2-) is mainly in the UV region below 400 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…In a previous report we showed that the visible light absorption is mainly arising from O-V LMCT transitions. 24 Notably, {VMo 5 } shows the lowest light absorption in the visible range between λ = 400-500 nm amongst the compounds investigated, see Fig. 2.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous report we showed that the visible light absorption is mainly arising from O-V LMCT transitions. 24 Notably, {VMo 5 } shows the lowest light absorption in the visible range between λ = 400-500 nm amongst the compounds investigated, see Fig. 2.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…POMs were reported. 24 To this end, the standard photooxidation conditions (see above) were used, but the samples were de-aerated by flushing with argon for 10 min prior to the experiment. During the photooxidation, the samples were kept under argon.…”
Section: De-aerated Conditionsmentioning
confidence: 99%
See 3 more Smart Citations